2009
DOI: 10.2105/ajph.2008.133827
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Early Head Start Children: A Qualitative Study of Staff, Parents, and Pregnant Women

Abstract: Tailored, theory-based interventions are needed to improve communication between EHS staff and families. Clear policies on the application of Head Start oral health performance standards to EHS are warranted. Educational activities should address the needs and suggestions of EHS participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 14 publications
4
31
0
5
Order By: Relevance
“…The specific areas of interest for the discussion were introduced using a semi-structured topic guide (Table 1). This was a short set of pre-selected topics that comprised open-ended questions based on previous work with similar groups in other countries [23,24,29,30]. These questions were revised so that they would be culturally compatible and reflect the Trinidadian context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific areas of interest for the discussion were introduced using a semi-structured topic guide (Table 1). This was a short set of pre-selected topics that comprised open-ended questions based on previous work with similar groups in other countries [23,24,29,30]. These questions were revised so that they would be culturally compatible and reflect the Trinidadian context.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative studies of low-income families in Head Start programs in the US report that parents often saw the primary dentition as temporary teeth whose condition had little bearing on the future dentition [24] and though aware of some of the problems that could arise felt that general life demands made oral care a low priority [24]. Daly et al [25] found that parents in their study (white mothers attending a Sure-Start program in the UK), viewed the primary dentition as important and were keen to establish good oral health habits.…”
Section: Introductionmentioning
confidence: 99%
“…Dental treatment is associated with improved OHRQoL [13–16], but outcomes can vary by the characteristics of families seeking treatment, including socioeconomic status and oral health literacy [17, 18]. The impact of clinical conditions on OHRQoL also can extend to the process of accessing treatment, which in and of itself can have a negative impact on low-income families, particularly when access to care is limited as it is with dentistry [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, some participants mentioned laziness as a reason for missing appointments, which reflects common stereotypes about poverty [26]. It also echoes the painful sentiment of people on social assistance: they feel misunderstood by oral health professionals [10,13,14,27] and, in a more general way, by society at large [28,29]. In fact, many people on social assistance actually work several hours per week in work reintegration programs, and therefore have limited availability for appointments during the day.…”
Section: Discussionmentioning
confidence: 99%